(untitled) (Journal of Intellectual Disability - Diagnosis and Treatment, 2024)
This study investigates the progression of paranoid personality disorder (PPD) and its influence on social interactions. Contemporary research indicates that genetic predispositions and extrinsic variables, such as crisis events, play a role in the development of PPD. Individuals with PPD frequently struggle to form enduring social relationships as a result of their prevailing negative thoughts, hostility, and unwillingness to compromise. The study emphasizes the need for prompt psychological support in overcoming stereotyped cognition and diminishing social seclusion among individuals with personality disorders. The study employs a theoretical and methodological framework that integrates analytical research methodologies and content analysis of psychotherapy interventions for individuals with neuropsychiatric conditions. The findings uncover challenges about psychological adjustment, emotional control, and interpersonal communication abilities among patients with PPD. This article also presents contemporary psychotherapy approaches that aid in recovering mental well-being. Furthermore, a pragmatic framework for the diagnosis and treatment of PPD in psychotherapy has been created. The findings collected in this study hold great importance for professionals in the fields of education and social work, as well as practical value for psychologists and psychotherapists who offer support to those at risk of developing neuropsychiatric illnesses.